Long term efficacy of recession and resection for abducens nerve palsy with targeting overcorrection of 5 prism diopters - Akinari Yamamoto; Manabu Miyata; Shinya Nakao; Kentaro Kawai; Kenji Suda; Eri Nakano; Miho Tagawa; Akitaka Tsujikawa (Scientific Reports, 2025)
Abstract Strabismus surgery is required for some cases with abducens nerve palsy (ANP) without spontaneous resolution; however, whether the surgical corrective effect for ANP is similar to that of concomitant esotropia (ET) remains unclear. This study compared the 1-year surgical outcomes of recession and resection (RR) between patients with ANP (ANP group, 11 patients) and those with concomitant ET (ET group, 33 patients). The target angle of RR for ANP was added by 5 prism diopters (Δ) compared to concomitant ET. The 1-year corrective effect was relatively lower in the ANP group than in the ET group (2.1 ± 0.7 Δ/mm vs. 2.6 ± 0.6 Δ/mm, P = 0.07), but the 3-month effect was similar (2.3 ± 0.6 Δ/mm vs. 2.6 ± 0.6 Δ/mm, P = 0.31) because significantly larger drift occurred in the ANP group than in the ET group (2.3 ± 2.2 Δ vs. 0.2 ± 2.7 Δ, P = 0.03). Motor success at 1 year was achieved in 90.9% of patients in both groups. Our findings suggested that the target angle of RR was suitable to add by 5 Δ in patients with ANP compared to concomitant ET in order to maintain a long-term favorable ocular position.